An Acoustic Analysis of Chinese Indonesian Students in Pronouncing English Vowels: A Praat Study - Teguh Perdana Damanik; Rahmadsyah Rangkuti; Rohani Ganie (Indonesian Journal of EFL and Linguistics, 2023)
This research aims to describe the errors made by Chinese-Indonesian students of the English Department of the University of Sumatera Utara in pronouncing English vowels; to discuss the reason for those errors this research uses Richard’s theory on causes of errors; and to overcome those errors using the phonetics transcription method and repetition drills. This research uses the Praat software to analyze the phonemes through the samples’ voice recordings. This research is qualitative and quantitative research. The data of this research are voice recordings of the samples and native speakers and the questionnaire answers of the samples. It is found that the Chinese-Indonesian students of the English Department who have passed the phonology subject still produce errors in pronouncing English vowels. It is concluded that these errors are found due to the effect of their mother tongues, namely Hokkien-Indonesian. The errors are also caused by the samples’ intralingual and developmental errors. In order to overcome those errors, this research employed the phonetic transcriptions method and repetition drills and found that the methods improve the overall values of selected English vowel phonemes.